2018
DOI: 10.1038/s41598-018-33893-y
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation confers beneficial metabolic effects of diet and exercise on diet-induced obese mice

Abstract: Diet and exercise are conventional methods for controlling body weight and are linked to alterations in gut microbiota. However, the associations of diet, exercise, and gut microbiota in the control of obesity remain largely unknown. In the present study, using 16S rRNA amplicon sequencing and fecal microbiota transplantation (FMT), normal fat diet (NFD), exercise and their combination resulted in improved metabolic profiles in comparison to sedentary lifestyle with high fat diet (HFD). Moreover, diet exerted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 67 publications
6
106
0
Order By: Relevance
“…Others have also reported that elite athletes have higher alpha diversity than sedentary controls (92), or that exercise training in mice leads to increased Shannon diversity (93,94). However, in agreement with the current experiment, PA has been shown to have no effect on alpha diversity in mice (29,95,96), rats (97), and humans (30,98). The reasons for these discrepancies are not clear, though multiple factors such as differences in animal vendors and facilities, DNA extraction methods and sequencing, bioinformatics analysis, and statistical testing methods, are likely involved.…”
Section: Wheel Running Has Limited But Significant Effects On the Intsupporting
confidence: 88%
“…Others have also reported that elite athletes have higher alpha diversity than sedentary controls (92), or that exercise training in mice leads to increased Shannon diversity (93,94). However, in agreement with the current experiment, PA has been shown to have no effect on alpha diversity in mice (29,95,96), rats (97), and humans (30,98). The reasons for these discrepancies are not clear, though multiple factors such as differences in animal vendors and facilities, DNA extraction methods and sequencing, bioinformatics analysis, and statistical testing methods, are likely involved.…”
Section: Wheel Running Has Limited But Significant Effects On the Intsupporting
confidence: 88%
“…61 Mice lacking fat mass-and the obesity-associated gene (Fto) exhibited reduced anxiety-and depression-like behavior, as well as a specific bacterial signature that suppresses inflammation, characterized by a lower abundance of Porphyromonadaceae and Helicobacter and a higher abundance of Lactobacilli. 63 Furthermore, the gut microbiota mediates the anti-obesity effect of calorie restriction in mice. 63 Furthermore, the gut microbiota mediates the anti-obesity effect of calorie restriction in mice.…”
Section: Pathog Ene S Is Of Non -Helicobac Ter Pylori Helicobac Termentioning
confidence: 99%
“…62 Fecal microbiota transplantation (FMT) has been reported to confer the beneficial metabolic effects of diet and exercise on diet-induced obese mice; these effects have been associated with bacterial genera including Helicobacters, in particular Helicobacter typhlonius, thus reflecting the genus vulnerability to diet, exercise, and even FMT. 63 Furthermore, the gut microbiota mediates the anti-obesity effect of calorie restriction in mice. 64 Indeed, calorie restriction has been shown to alter the composition of the gut microbiota with significant increases in probiotic genera and a decrease in harmful bacteria such as Helicobacters.…”
Section: Increasing Evidence Suggests That An Infection With a Gastricmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is a new and straightforward therapy that manipulates the gut microbiota by transferring healthy donor microbiota into an existing disrupted gut microbial ecosystem. This therapy can be an effective approach to obesity treatment [12,13]. Even though FMT has some limitations, several studies have tested its effectiveness and have demonstrated an improvement of some comorbidities associated not only with obesity [14] but also with other noncommunicable diseases [1518].…”
Section: Introductionmentioning
confidence: 99%